Δομική σημασιολογία και σχεδιασμός διαδραστικών εφαρμογών: ενημέρωση για την κατάθλιψη - Eleni D. Lazaridou (Syn-Thèses, 2023)
Narrative structures are sometimes used to make a communication process, such as a documentary or even a news report, more interesting (Ohler, 2008). The need for the systematic study of narrative structures and their interpretation led to the adoption of theories from the field of structural linguistics. A.J. Greimas proposed a model of semantic analysis of texts that studies the codes of the signified, denotative and connotative (Boklund-Lagopoulou, 1983), distinguishing the structural level of narrative discourse, namely the structural organization of the meaning of the text and the manifested text. In this case study, the Greimas’ semantic model is applied in conjunction with multimodality, with the aim of designing an interactive narrative about depression, based on the proposal of Maria-Ilia Katsaridou (2023). According to this proposal, the design of the interactive narrative starts from the level of depth and ends in the textualization. The interactive story is characterized by narrative coherence which contributes to the more effective transmission of information (Katsaridou, 2023), while the mental immersion and social awareness of the viewer is maximized due to the interaction with the gamified environment.